Field efficacy of some new insecticides against brinjal shoot and fruit borer, Leucinodes orbonalis (Guen.) (Lepidoptera: Pyralidae) and their toxic effects on natural enemies: Efficacy of new insecticides in controlling BSFB - Rahman, Mohammad Wasif; Das, Gopal; Uddin, Mohammad Mahir (Journal of the Bangladesh Agricultural University, 2019)
Brinjal is susceptible to attack of various insect pests from seedling to fruiting stage. Among these, brinjal shoot and fruit borer, Leucinodes orbonalis (Guen.) is the most destructive pest and is considered to be the limiting factor in quantitative as well asqualitative harvest of brinjal fruits. In the present study, efficacy of some new insecticides viz. Pine 6 WG (Emamectin benzoate + Abamectin), Heron 5 EC (Lufenuron), Belt 24 WG (Flubendiamide) and Cyclone 2.5 EC (Lambda-cyhalothrin) were evaluated against brinjal shoot and fruit borer (BSFB) in field condition from the period of October, 2015 to April, 2016. The experiment was laid out in a Randomized Complete Block Design (RCBD) having three replications and two concentrations of each of the insecticides. A total of three spraying was given and finally a cumulative mean was found out. Data were collected on percent shoot infestation, percent fruit infestation, marketable fruit yield (t/ha) and abundances of natural enemies per plant. Results clearly showed that all the insecticides significantly reduced BSFB infestation as well as increased marketable fruit yield compared to the untreated control. The highest shoot (27.40%) and fruit (55.93%) infestation were recorded from control plots. On the other hand, the lowest shoot (6.71%) and fruit (11.58%) infestation were recorded from Pine 6 WG treated plots @ 0.50 g/L that was followed by Heron 5 EC @ 1.0 ml/L (6.89% shoot; 14.51% fruits), Cyclone 2.5 EC @ 1.5 ml/L (15.73% shoot and 16.45% fruits) and Belt 24 WG @ 0.50 g/L (9.53% shoot and 25.47% fruits), respectively. Similar trend was found in case of marketable fruit yield as well. Pine 6 WG and Heron 5 EC were found to be comparatively safe for both ladybird beetle and lynx spiders as their abundances were not changed significantly compared to untreated control. In contrast, the application of Belt 24 WG and Cyclone 2.5 EC has reduced 50 to 60% of the ladybird beetle and lynx spiders populations in brinjal eco-system. The results suggested that two biopesticides viz., Pine 6 WG and Heron 5 EC can be used successfully against BSFB considering minimum shoot and fruit infestation, higher fruit yield and less toxicity to natural enemies in brinjal eco-system. J Bangladesh Agril Univ 17(3): 319–324, 2019